Remittances and regional economic growth in Colombia 2009 - 2016: a panel data application - Chamorro-García, Andrés Fernando; Hernandez Garcia, Edwin Arbey (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The main objective of the article is to determine the impact of remittances on the economic growth of the regions in Colombia, taking into account the panel data structure for the period 2009-2016. Are used the data of international remittance income from the Banco de la República and the Gross Domestic Product of the Colombian regions published by the Departamento Administrativo Nacional de Estadística (DANE), from which econometric equations are estimated using the estimator of fixed effects corrected by autocorrelation and heteroscedasticity for panel data. The results show a positive and significant effect of remittances on regional economic growth.